Giving medical evidence in court. Issue 4 (April 2022) - Doye, Aidan; Metcalfe, Neil; Hudson QC, Chloe
Doctors provide an invaluable role in the justice system. Acting as a witness can be both a beneficial experience for the individual and of importance in representing the profession. This article will explore the different roles doctors play in court and the challenges involved, as well as reviewing current guidance for giving evidence in the courts. Doctors are not only being sued more often, but are also called on more often as expert witnesses in court, and GPs should be aware of this role and the responsibilities involved.